Who is delivering the Australian BA? Trends in staff profiles of academics in the BA. - Gannaway, Deanne; Trent, Faith; Upton, Hayley; Price, Sarah (Australian Learning and Teaching Council, 2008)
Report from a project that aimed: To understand the nature and role of a Bachelor of Arts degree in contemporary Australia; To map the diverse Bachelor of Arts programs on offer in Australia between 2001-2008; To identify the major strengths, difficulties, capabilities and contributions of the program; and to provide rich base-line data on the nature and models of BAs to be accessible for future curriculum planning for arts faculties. This report presents national staffing trends within BA programs across Australia. The project drew upon demographic data collected for DEST/DEEWR gathered during 2001 – 2006.